Genetic analysis of drought and heat tolerance combined with Striga hermonthica resistance in tropical maize (Zea mays) - Melkamu Elmyhun; Ermias Abate; Alemu Abate; Adefris Teklewold; Silvestro Meseka; Abebe Menkir (PLoS ONE, 2026)
The occurrence of combined biotic and abiotic stresses with more damaging effect is worsening in maize production fields in SSA due to climate change. The development of multiple stress tolerant maize hybrids is thus critical to assure food security. This study was conducted to (i) examine the mode of inheritance of combined tolerance to drought and heat stress (CDHS) with resistance to Striga in tropical maize and (ii) assess the feasibility of selecting hybrids with combined tolerance to drought and heat stress and resistance to Striga infection. Single cross hybrids formed from Striga resistant lines with contrasting resistance reactions to tassel blasting were then evaluated under combined drought and heat stress as well as under Striga infested (STIN) and non-infested (STNO) conditions. The observed high GCA/SCA ratio and narrow sense heritability estimates indicated that additive gene action had a major effect on the inheritance of most traits under all testing conditions. Seven parental lines had positive GCA effects for grain yield under CDHS and STIN conditions when they were used as both male and female parents. We also found single crosses with positive specific combining ability (SCA) for grain yield. Grain yield under STIN had positive and significant genotypic and phenotypic correlations with yield recorded under CDHS and STNO conditions. It thus appears that grain yield may be regulated by common alleles across the three growing conditions. Selected parental lines are potential parents for developing source populations of new inbred lines and superior hybrids with combined CDHS tolerance and Striga resistance. Promising single crosses could be used as female parents to develop multiple stress tolerant 3-way cross hybrids.